Allergen Risk Assessment for Specific Allergy to Small Ruminant's Milk: Development of Sensitive Immunoassays to Detect Goat's and Sheep's Milk Contaminations in Dairy Food Matrices - Bernard, Hervé; Hazebrouck, Stéphane; Gaiani, Nicolas; Adel-Patient, Karine (Frontiers in Allergy, 2021)
Despite a high level of sequence identity between cow’s, goat’s and sheep’s milk (CM, GM and SM, respectively) proteins, some patients tolerant to CM are allergic to GM and SM. In most cases, this specificity is due to the presence of IgE antibodies that bind only to caprine and ovine caseins. The patients may then develop severe allergic reactions after ingestion of CM products contaminated with low amounts of GM or SM. We thus aimed to develop an assay able to detect traces of caprine/ovine β-caseins in different food matrices, irrespective of the presence of the bovine homologue. We produced monoclonal antibodies (mAbs) specific to caprine caseins in mice tolerized to the bovine whole casein then sensitized to the caprine whole casein. In order to develop a two-site immunometric assay, we selected mAbs that could discriminate the caprine β-casein from its bovine homologue. Characteristics and performances of two tests were determined with various dairy products. Results were analyzed in relation with the IgE-immunoreactivity of the food matrices, thanks to sera from CM, GM/SM allergic patients. Our two-site immunometric assays demonstrated a high sensitivity with a detection limit of 1.6 to 3.2 ng/mL of caprine and ovine β-caseins. The tests were able to detect contaminations of GM in CM at the ppm level. Heat-treatment, ripening and coagulation processes, usually applied to dairy products that exhibit a very high IgE-immunoreactivity, did not impair the test sensitivity. These quantitative assays could then be useful for the risk assessment of food products potentially contaminated with GM and SM in order to prevent adverse reactions in patients specifically allergic to these milks.